Physical and numerical modelling of wave interaction with a three-dimensional submerged structure - Baker, Scott (University of Ottawa (Canada), 2008)
Submerged structures are frequently used in coastal engineering applications, such as tunnel and pipeline protection works, breakwaters, and artificial reefs. Although a significant number of research works have focused on low-crested structures, there is far less research into deeply submerged structures. In most research, lightly-sloped, uniform cross-sectioned submerged structures with specific crest elevations are considered. The present thesis deals with the three-dimensional physical and numerical modelling of the interaction of irregular waves with a large-scale three-dimensional submerged structure. It aims to advance the understanding of the structure's influence on the irregular wave field, the wave-induced velocities along the structure crest, and the wave-induced currents. The ability of a nonlinear Boussinesq wave model to simulate these processes is also investigated and assessed. Analysis was performed on a multitude of data, including---but not limited to---wave heights, wave periods, wave energy spectra, energy transfer functions, reflection analyses, and wave-induced velocities. In general, the analysis and comparison performed showed that the numerical model provided a modestly accurate representation of the physical modelling results.
Keywords: Engineering, Civil.; Engineering, Marine and Ocean.